Analisis Komparatif Dakwah Moderasi Beragama pada Akun Istagram Muhammadiyah Garis Lucu dan NU Garis Lucu - Fasadena, Nova Saha (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study aims to conduct a comparative analysis of religious moderation campaigns promoted by two popular Instagram accounts, Muhammadiyah Garis Lucu and NU Garis Lucu. These accounts creatively deliver religious messages in a humorous context that resonates with a wide audience, particularly the younger generation. Religious moderation has become an increasingly relevant issue in the face of diverse religious understandings in Indonesia, where inclusive and tolerant approaches to religious outreach are greatly needed. The method employed in this research is qualitative content analysis of the posts from both accounts, focusing on messages related to religious moderation. The study found that while both accounts use humor, they differ in their approach to conveying messages of moderation. Muhammadiyah Garis Lucu emphasizes rationality, while NU Garis Lucu focuses more on tradition. This study concludes that a humorous approach in religious outreach can be an effective means of conveying messages of moderation; however, more consistent strategies are required to ensure these messages are well-received by a diverse audience.